Learning from mRNA: the relevance of the tumour suppressor protein UPF1’s internal ribosome entry site-mediated translation in tumorigenesis - Lacerda, Rafaela (2021)
Crucial in several cellular processes, such as nonsense-mediated mRNA decay, cell cycle progression, and telomere maintenance and homeostasis, Up-frameshift 1 (UPF1) has also been considered a tumour suppressor protein in hepatocellular carcinoma and gastric cancer, as it is underexpressed in the latter and negatively correlated to MALAT1 (long non-coding RNA metastasis-associated lung adenocarcinoma transcript 1) expression. UPF1 overexpression inhibits some cancer-specific features, like proliferation, cell cycle progression, cell migration and invasion, and enhances apoptosis, turning the UPF1/MALAT1 pathway a potential therapeutic target for gastric cancer. Here, we investigate the importance of UPF1 internal ribosome entry site (IRES)-dependent translation in tumorigenesis, specifically in colorectal cancer. Thus, we used a bicistronic system with two reporter genes, in which we cloned UPF1 5’ untranslated region (UTR) upstream the second cistron, whose translation will only occur internally. We transcribed the bicistronic mRNA in vitro and transfected HeLa (cervical cancer), NCM460 (normal intestinal-derived colonocytes) and HC116 (pre-metastatic colorectal carcinoma) cells with such mRNA, along with the positive and negative controls. The results show a significant increase in IRES-mediated translation levels compared to those of the negative control, both in normal conditions and under endoplasmic reticulum stress. Also, internal initiation occurs in the absence of the cap structure. Deletional and mutational analysis of UPF1 5’UTR showed that nucleotides 1–100 (stem loop (SL) I) and 151–275 (SL III) — out of 275 nucleotides — are the minimal required sequences for the IRES to work properly. Also, we used RNA antisense oligonucleotides (ASOs) targeting UPF1 IRES SL I and III, and observed a reduced UPF1 expression. Cellular viability increases in HCT116 cells and decreases in NCM460 cells treated with ASOs targeting SL III and SL I, respectively, whereas apoptosis increases in NCM460 cells and decreases in HCT116 cells treated with ASOs targeting SL I. This may be the dawn of a new RNA-based therapeutic approach regulating colorectal cancer development.